2022
DOI: 10.18280/mmep.090317
|View full text |Cite
|
Sign up to set email alerts
|

Performance Examinations of Quadrotor with Sliding Mode Control-Neural Network on Various Trajectory and Conditions

Abstract: In this article, the performance of the sliding mode control (SMC) that is combined with the backpropagation neural network (NN) as the main control of quadrotor’s dynamic systems was examined on various trajectories and conditions, through numerical simulation. The simulation is conducted with three different trajectories in the absence and presence of the time-varying external disturbances that were adopted from previous studies. The time-varying external disturbances are implemented for the roll, pitch, yaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Zhao and Jin [30] proposed a SMC algorithm based on Radial Basis Function Neural Network (RBFNN) to eliminate the effects of model uncertainties and exogenous disturbances on the path tracking controller of agricultural quadcopter with variable payload, and verified the efficacy and more accurate path tracking performance of the proposed controller by comparing it experimentally with other classic SMC methods. Darwito and Wahyuadnyana [31] combined SMC with Back Propagation Neural Network (BPNN) for trajectory tracking of quadcopters and simulated its effect, their results proved that the proposed scheme could control the quadcopter in absence and presence of time-varying external disturbances. Zare et al [32] integrated SMC with fuzzy logic based on Lyapunov function and optimized it using an intelligent fuzzy-genetic algorithm and applied it to quadcopter slung load position and attitude control, the proposed method exhibited good stability, robustness, and tracking performance in case of transient and steady states with external disturbances, and effectively reduced the chattering phenomenon.…”
Section: Literature Reviewmentioning
confidence: 96%
See 2 more Smart Citations
“…Zhao and Jin [30] proposed a SMC algorithm based on Radial Basis Function Neural Network (RBFNN) to eliminate the effects of model uncertainties and exogenous disturbances on the path tracking controller of agricultural quadcopter with variable payload, and verified the efficacy and more accurate path tracking performance of the proposed controller by comparing it experimentally with other classic SMC methods. Darwito and Wahyuadnyana [31] combined SMC with Back Propagation Neural Network (BPNN) for trajectory tracking of quadcopters and simulated its effect, their results proved that the proposed scheme could control the quadcopter in absence and presence of time-varying external disturbances. Zare et al [32] integrated SMC with fuzzy logic based on Lyapunov function and optimized it using an intelligent fuzzy-genetic algorithm and applied it to quadcopter slung load position and attitude control, the proposed method exhibited good stability, robustness, and tracking performance in case of transient and steady states with external disturbances, and effectively reduced the chattering phenomenon.…”
Section: Literature Reviewmentioning
confidence: 96%
“…(3) The proposed ANFIS-SMC scheme of quadcopter controller was compared with the SMC method proposed in [31] and its effectiveness and superiority were verified via simulation results.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To control a quadcopter a new controller based on emotional learning was proposed a novel bidirectional algorithm for emotional learning is used in conjunction with an easier fuzzy neural network within the confines of this feature technique, the outcomes showed that the suggested approach performed admirably, as shown by the findings [10]. While in reference [11], sliding mode control using neural network backpropagation using three alternative paths and numerous circumstances with and without external disturbances was examined. Simulated results using MATLAB prove the SMC-NN control system's tracking performance and capacity to reach the target trajectory in the face of external disturbances.…”
Section: Figure 1 Categorization Of Control Techniquesmentioning
confidence: 99%
“…The robustness is an attractive property of the SMC method. However, as noted in the literature [35][36][37], the fundamental problem of the SMC approach is that it causes chattering, or high frequency in the control input signal. To overcome the disadvantage, fractional order sliding mode control (FOSMC) is proposed as one of the enhanced versions of the SMC method.…”
Section: Introductionmentioning
confidence: 99%